Studi cohort: prevalensi osteoporosis pada usia lanjut di Yogyakarta - Mirza Hapsari Sakti Titis Penggalih, Hamam Hadi dan Retno Pangastuti (Berita Kedokteran Masyarakat (BKM), 2005)
Background: The increase in the number of elderly in Indonesia, especially in Yogyakarta requires certain consequence in solving all the problems about elderly in cases of health problem. It affects the morbidity of elderly which one of the problems is caused by osteoporosis. The treatment and examination of osteoporosis has been doing by Klinik Lanjut Usia FK-UGM Yogyakarta recently, but there are lack of information about the prevalence of osteoporosis in Yogyakarta. Objective: The aim of this research is to provide the information about the prevalence of osteoporosis. Methods: This research is an observational research with cohort retrospective design. The subject is all patient who attended in Klinik Lanjut Usia FK-UGM. The criteria are > 60 years old and > 2 times Bone Mass Density examination. There were 142 patients who were involved in this research. We collected the secondary data with data collecting form. We analyzed it as the prevalence of osteoporosis. Results: The result of analysis shows that the prevalence of osteoporosis is 59.86 %. Conclusions: The high prevalence of osteoporosis (59.86%) can been cut down by the therapies through the holistic education by health worker. The action needs to be controlled routinely to know the patients progress. Health promotion should involved in this action to give a clear information about what can be allowed to do by people. Keywords: prevalence, osteoporosis, elderly